Synthesis of Hybrid CdS−Au Colloidal Nanostructures - Saunders, Aaron E; Popov, Inna; Banin, Uri (The journal of physical chemistry. B, 2006)
We explore the growth mechanism of gold nanocrystals onto preformed cadmium sulfide nanorods to form hybrid metal nanocrystal/semiconductor nanorod colloids. By manipulating the growth conditions, it is possible to obtain nanostructures exhibiting Au nanocrystal growth at only one nanorod tip, at both tips, or at multiple locations along the nanorod surface. Under anaerobic conditions, Au growth occurs only at one tip of the nanorods, producing asymmetric structures. In contrast, the presence of oxygen and trace amounts of water during the reaction promotes etching of the nanorod surface, providing additional sites for metal deposition. Three growth stages are observed when Au growth is performed under air:  (1) Au nanocrystal formation at both nanorod tips, (2) growth onto defect sites on the nanorod surface, and finally (3) a ripening process in which one nanocrystal tip grows at the expense of the other particles present on the nanorod. Analysis of the hybrid nanostructures by high-resolution TEM shows that there is no preferred orientation between the Au nanocrystal and the CdS nanorod, indicating that growth is nonepitaxial. The optical signatures of the nanocrystals and the nanorods (i.e., the surface plasmon and first exciton transition peaks, respectively) are spectrally distinct, allowing the different stages of the growth process to be easily monitored. The initial CdS nanorods exhibit band gap and trap state emission, both of which are quenched during Au growth.